RESPON KREDIT BANK KONVENSIONAL TERHADAP KEBIJAKAN MONETER DI INDONESIA TAHUN 2011-2013 (STUDI PADA BANK PLAT MERAH DAN BUSN) - Tobing, Maureen Inesella Lumban (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
The study examines the problem of how the transmission of monetary policy through the lending channel can be addressed by conventional banks in Indonesia. In fact, many studies were conducted to examine the monetary transmission of lending channel has resulted in different conclusions. There are at least two conflicting opinions, first: the lending channel through a bank can work with small asset or capitalization; and second: this transmission cannot work through a bank that has large asset or capitalization. The method used in this study is panel regression. In this present study, the data were obtained from the monthly period between 2011:1 to 2013:12. Fourteen conventional banks publicized on the website of Bank Indonesia were observed. This study found that the transmission of lending channel can work on a conventional bank that has a small asset or capitalization. In contrast, for a conventional bank that has large and small asset or capitalization is not working in Indonesia.Kata kunci: Monetary Policy, Bank Lending Channel, Conventional Bank